IMPROVING STUDENTS SPELLING SKILLS THROUGH USING JOLLY PHONICS METHOD (AGE 5 YEARS) - Yakoba Novena Srikandewie; Yon A. E. (Dialectical Literature and Educational Journal, 2021)
This research describes a classroom action research (CAR) held in Bilingual Kindergarten, Gambir - DKI Jakarta, through the implementation of Jolly Phonics Method to improve the basic ability in spelling using the letter sounds. There are 10 students as a population in one class for K2 level (age 5 years). In this research article, the writer used qualitative method and experimental method to get the data. The major goal of Jolly Phonics method teaching, students have achievements are much greater in both reading and writing relating the letter sounds based on students spelling skills. This research was conducted in two cycles. Each cycle included four stages: planning, observing, improving, and practicing. The data were obtained by the result of pre-cycle, cycle I and cycle II. The finding result of the students of at pre-cycle was 63, then increase to 68 for the first cycle, the last increase up to 73 for the second cycle.  The teaching of Jolly Phonics includes 5 teaching points. Those are learning the letter sounds, learning letter formation, blending, identifying sounds in words, and tricky words.  The data that were obtained qualitatively and quantitatively show that Jolly Phonics Method could improve: (l) the students’ ability in remembering the letter that represent of each sound is taught with an action, (2) the students’ ability in pronouncing the letter sounds correctly, (3) the students’ ability in spelling the words correctly. The major goal and result of Jolly Phonics method that students have achievements are much greater in both reading and writing relating the letter sounds based on students spelling skills.